Exploring Chemical and Physical Advancements in Surface Modification Techniques of Natural Fiber Reinforced Composite: A Comprehensive Review - Mohammadi, Majid; Ishak, Mohamad Ridzwan; Sultan, Mohamed Thariq Hameed (Journal of natural fibers, 2024)
This review presents a comprehensive overview of recent trends, advances, and challenges in the use of natural fiber composites. This section begins by discussing the growing adoption of bio-based fibers because of their eco-friendly nature and cost-efficiency, focusing particularly on plant-based fibers. A bibliometric analysis will be conducted to evaluate the publication frequency and research trends in this domain. Furthermore, the structural compositions of natural fibers, including cellulose, hemicellulose, lignin, pectin, and wax, were elucidated, highlighting their significance in composite material engineering. The extraction methods of natural fibers, including retting and mechanical decortication, are discussed, along with their implications for fiber quality. The limitations associated with natural fibers, including their hydrophilicity and poor mechanical properties, compared with their synthetic counterparts are addressed. Various surface-treatment methods, particularly physical and chemical ones, were explored to enhance fiber compatibility with polymer matrices. The abstract delves into the principles, techniques, and effects of physical and chemical treatments on natural fibers, emphasizing their role in improving the surface characteristics, interfacial adhesion, and overall mechanical properties of composites. Furthermore, specific studies investigating the impact of physical and chemical treatments on natural fibers are summarized, elucidating the observed changes in fiber morphology, chemical composition, and mechanical properties.